Adaptive Governance Planning Strategies in Green Open Spaces in Makassar - Zulvan Naharuddin Naharuddin; Oky Nur Pratiwi Johansyah (Universitas Negeri Makassar, 2023)
AbstractThis research aims to find out Adaptive Governance Planning Strategies in Green Open Spaces in Makassar. This study uses a qualitative technique to investigate decision-making transparency, responsiveness issues, inclusivity, spatial concerns, and community involvement tactics in relation to the adaptive governance of green open spaces in Makassar. Even with strong decision transparency, there are still issues with inclusivity and responsiveness, which highlights the necessity for dynamic governance. The study recognizes the different sizes of green spaces in Makassar and emphasizes the importance of spatially aware planning. Diverse tastes should be accommodated by community engagement techniques. Studies that have been compared to one another show both consistency and distinct environmental elements. Planning that is appropriate for the situation, dynamic interaction platforms, and continuous training are examples of constructive suggestions. All things considered, the results add significant knowledge to the conversation about adaptive governance and point planners, policymakers, and communities in the direction of a resilient and sustainable future for Makassar's green open spaces.